2016
DOI: 10.1016/j.actamat.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Expanding time–temperature-transformation (TTT) diagrams to interfaces: A new approach for grain boundary engineering

Abstract: Bulk phase transformation kinetics were not well understood before Davenport and Bain developed time-temperature-transformation (TTT) diagrams for steel alloys in the 1930s. These powerful diagrams revolutionized the heat treatment of steel and other alloys. Grain boundaries and internal interfaces are now known to behave in a phase-like manner, referred to as 'complexions', and their transitions can be represented on TTT diagrams. We present experimental grain boundary complexion TTT diagrams for polycrystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 18 publications
5
49
0
Order By: Relevance
“…Conceptually, the distinct interface structures observed in both alloys are similar to the formation of interface ‘complexions' which have been identified in the case of grain boundaries in several ceramic and metallic systems2728. Complexions are ‘interface-stabilized states'29 that have a structure and composition different from that of the matrix and remain confined in the region where they form.…”
Section: Discussionsupporting
confidence: 53%
“…Conceptually, the distinct interface structures observed in both alloys are similar to the formation of interface ‘complexions' which have been identified in the case of grain boundaries in several ceramic and metallic systems2728. Complexions are ‘interface-stabilized states'29 that have a structure and composition different from that of the matrix and remain confined in the region where they form.…”
Section: Discussionsupporting
confidence: 53%
“…1(b), the a + b microstructure is metastable above T C for short times. Complexion TTT diagrams exhibit analogous regions of metastability [5], suggesting that they undergo nucleation and growth processes similar to those characteristic of bulk phases. One signature of a grain-boundary complexion transition is the appearance of abnormally large grains [3,6], and experiments have shown that the number density of abnormal grains increases exponentially with temperature [7], an observation that is consistent with a nucleation and growth mechanism.…”
Section: Introductionmentioning
confidence: 92%
“…Just as with bulk phase transformations, complexion transitions take time to occur, and therefore their kinetics can be represented on TTT-style diagrams. The first experimental complexion TTT diagrams were recently reported based on grain growth studies of polycrystalline Y 2 O 3 and Al 2 O 3 [5]. These diagrams clearly show the combinations of time and temperature at which grain-boundary complexion transitions occur, unifying and displaying a large data set in a readily understood format.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interesting attempts have been implemented by researchers (e.g., Cantwell et al, 2016 andGuo et al, 2015), who investigated the grain size variations through electron scanning techniques. Also, studies in steel features under fire conditions presented by Digges et al (1966), Smith et al (1981), Kirby et al (1986) and Tide (1998).…”
Section: Studies On Mechanical Propertiesmentioning
confidence: 99%